Students’ Perception on Career in Romania and Portugal – a Comparative Analysis - Alecxandrina DEACONU; Cătălina RADU; Maria CONCEIÇÃO Ramos (Revista de Management Comparat International)
The dynamics, the turbulence and the incertitude from the business environment significantly change the perception of the young on career, amplifying their motivation and interest for competence but also the preoccupation for a good knowledge of the opportunities and threats from the labour market. In this article we aim to identify the orientations of the students from the economic field in regards to their own career and to make a comparative analysis of the outcome of a quantitative research undertaken this year, in two economic universities from two states of the European Union facing similar economic and social phenomena. The conclusions of this study represent a solid base to initiate certain actions, with the help of which the university could significantly contribute to the career success of future graduates.